Phenotypic characteristics of familial glucocorticoid deficiency (FGD) type 1 and 2 - Chung, Teng-Teng L L (Blackwell Publishing Ltd, 2010)
CONTEXT: Familial glucocorticoid deficiency (FGD) is a rare autosomal recessive disorder as a result of mutation in genes encoding either the ACTH receptor [melanocortin 2 receptor (MC2R)] or its accessory protein [melanocortin 2 receptor accessory protein (MRAP)[. The disorder is known as FGD type 1 and 2, respectively. OBJECTIVE: The aim of the study was to compare the phenotype/genotype relationships between FGD 1 and 2. DESIGN AND PATIENTS: Forty patients with missense MC2R mutations and 22 patients with MRAP mutations were included. Forty-four of these patients had been referred for genetic screening and 18 were patients published by other authors. RESULTS: The median age at presentation for FGD type 1 was variable at 2·0 years; range 0·02–16 years, and this was associated with unusually tall stature, mean height SDS + 1·75 ± 1·53 (mean ± SD). In contrast, FGD type 2 presented at a much earlier median age (0·08 years; range at birth to 1·6 years) (P < 0·01) and patients were of normal height SDS + 0·12 ± 1·35 (P < 0·001). No differences in baseline cortisol or ACTH levels were seen between FGD types 1 and 2. CONCLUSION: FGD type 2 appears to present earlier. This may reflect the functional significance of the underlying mutations in that all MRAP mutations are nonsense or splice site mutations that result in abolition of a functional protein, whereas most of the MC2R mutations are missense mutations and give rise to proteins with some residual function. Tall stature is associated with mutations in MC2R but not in MRAP. There were no other significant clinical distinctions between the two.